Genome-wide identification and expression analysis of phosphate-sensing SPX proteins in oats - Du, Yinke; Gong, Jie; Dou, Ziyi; Zheng, Wei; Sun, Renwei; Gao, Shiqing (Frontiers in Genetics, 2024)
Phosphorus is indispensable to plant growth and development. Soil phosphorus deficiency poses a substantial constraint on crop yield. SPXs play pivotal roles in phosphate transport and absorption in plants. Yet, the functions of SPXs of oat (Avena sativa L.) under abiotic stresses remain unclear. In this study, we conducted a genome-wide analysis of 169 SPXs from hexaploid oat and five closely related plant species. All homologous AsSPXs were found to arise from duplication events and depict a strong purifying selection. Subcellular localization prediction revealed that AsSPXs were mainly located on the plasma membrane. Seventeen cis-acting elements, predominantly comprising light-, low temperature-, abscisic acid-, and drought-responsive elements, were dispersed in the promoter regions of AsSPXs. Analysis of cis-regulatory elements, protein-protein interaction networks, and qRT-PCR showed that AsSPXs are not solely involved in phosphorus starvation response but also in various stress responses. Notably, AsSPX18-5D (AVESA.00001b.r3.5Dg0002895) exerted pivotal roles in conferring resistance against low phosphorus, salt, and ABA treatments. Our study aimed to explore important stress-resistant genes in oat. Our results could provide a basis for future studies on the evolution and functions of the AsSPX gene family and a crucial foundation for comprehending how oat responds to environmental stresses.